Why religious freedom matters for democracy: comparative reflections from Britain and France for a democratic "vivre ensemble" - Hunter-Henin, Myriam (Hart studies in comparative public law, 2020)
Introduction -- Contextual Analyses : Laïcité and the Democratic Vivre Ensemble -- Contextual Analyses : The English Experience of Vivre Ensemble -- Conceptual Framework : The Liberal Democratic Vivre Ensemble -- Lessons from Achbita -- Beyond Achbita : Possible Ways Forward -- Conclusion.